1900-1945 : Künstler in Deutschland : Individualismus und Tradition. - Osterwold, Tilman; Württembergischer Kunstverein, Stuttgart (Stuttgart : Edition Cantz, 1986)
Corinth, Lovis ; Modersohn-Becker, Paula ; Nolde, Emil ; Schmidt-Rottluff, Karl ; Kircher, Ernst Ludwig ; Mueller, Otto ; Kokoschka, Oskar ; Hölzel, Adolf ; Macke, August ; Marc, Franz ; Jawlensky, Alexej ; Kandinsky, Wassily ; Klee, Paul ; Ernst, Max ; Schwitters, Kurt ; Moholy-Nagy, Laszlo ; Dexel, Walter ; Schlemmer, Oskar ; Belling, Rudolf ; Lehmbruck, Wilhelm ; Meidner, Ludwig ; Dix, Otto ; Grosz, George ; Radziwill, Franz ; Schad, Christian ; Scharl, Josef ; Pankok, Otto ; Barlach, Ernst ; Kollwitz, Käthe ; Beckmann, Max ; Hartung, Hans ; Uhlmann, Hans ; Winter, Fritz ; Nay, Ernst Wilhelm ; Baumeister, Willi
1900-1945 : Künstler in Deutschland : Individualismus und Tradition, Württembergischer Kunstverein, Stuttgart, 18.9. - 9.11.1986
kunstcatalogus
Keywords: Duitsland